The Role of Interleukin 17 in Tumour Proliferation, Angiogenesis, and Metastasis. (7th July 2014) - Yang, Bob; Kang, Heechan; Fung, Anthony; Zhao, Hailin; Wang, Tianlong; Ma, Daqing
Abstract : With 7.6 million deaths globally, cancer according to the World Health Organisation is still one of the leading causes of death worldwide. Interleukin 17 (IL-17) is a cytokine produced by Th17 cells, a T helper cell subset developed from an activated CD4+ T-cell. Whilst the importance of IL-17 in human autoimmune disease, inflammation, and pathogen defence reactions has already been established, its potential role in cancer progression still needs to be updated. Interestingly studies have demonstrated that IL-17 plays an intricate role in the pathophysiology of cancer, from tumorigenesis, proliferation, angiogenesis, and metastasis, to adapting the tumour in its ability to confer upon itself both immune, and chemotherapy resistance. This review will look into IL-17 and summarise the current information and data on its role in the pathophysiology of cancer as well as its potential application in the overall management of the disease.